If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -2(5x + -3) = 2(x + 9) Reorder the terms: 15x + -2(-3 + 5x) = 2(x + 9) 15x + (-3 * -2 + 5x * -2) = 2(x + 9) 15x + (6 + -10x) = 2(x + 9) Reorder the terms: 6 + 15x + -10x = 2(x + 9) Combine like terms: 15x + -10x = 5x 6 + 5x = 2(x + 9) Reorder the terms: 6 + 5x = 2(9 + x) 6 + 5x = (9 * 2 + x * 2) 6 + 5x = (18 + 2x) Solving 6 + 5x = 18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 6 + 5x + -2x = 18 + 2x + -2x Combine like terms: 5x + -2x = 3x 6 + 3x = 18 + 2x + -2x Combine like terms: 2x + -2x = 0 6 + 3x = 18 + 0 6 + 3x = 18 Add '-6' to each side of the equation. 6 + -6 + 3x = 18 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 18 + -6 3x = 18 + -6 Combine like terms: 18 + -6 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| 4(36-12h+h^2)-18+3h-(144-18)= | | -7+3x=-34 | | 28-3c=14 | | 5=6x-1 | | y=x^4+1x^2-30 | | P=20-5Q | | x^4+1x^2-30=0 | | (10x+9)=3 | | 3*5*6=153072 | | 5x-7=7x+6 | | 58=10x+8 | | 64x^4-27x=0 | | 11.5-8.5= | | 0=x^2-21x+24 | | 8-0.5(x+3)=0.25(x+-1) | | -(4-m)=10 | | 6=-4k+2 | | 20y+2=46 | | 1.33*4=y | | s*7-17=137 | | x^2+x+m-1=0 | | 5(x+3)-3=2(x+8) | | 43-4=y | | 9h-16=74 | | 9m-15=58 | | 5n^2+7n=-2 | | 8x+12y-20= | | 40+16x= | | 3(25-10h+h^2)-20+4h-(75-20)= | | 15x-28= | | 0=x^2-16x-225 | | 6x+27= |